Platform Tolerant RFID Tag Antenna Design for Safety and Real-Time Tracking of On-site Workers at Riskier Workplaces - Aarti Bansal; Rajesh Khanna; Surbhi Sharma (International Journal of Antennas and Propagation)
The safety of workers is significant when talking about large risky workplaces such as construction job sites. Therefore, we proposed a UHF-RFID tag antenna that can be used to identify various Job site equipments and also construction workers by tagging their wearable helmets. Here, the compact, low profile, and simple structured platform-tolerant RFID tag antenna is proposed and optimized for metal sheet and ABS-based safety helmets. Furthermore, WTMiddleware (Worker Tracking Middleware) using Javascript, CSS, and HTML has been implemented to demonstrate a real-time secured web-based remote access of workers to provide their actual on-site monitoring and tracking of construction equipment carried/operated by the workers for tracking solutions. First, the fabricated tag’s performance was tested successfully in an outdoor scenario on various mountable materials such as wood, glass, plastic, and metal. The tag yielded a reasonable read range of 5.9 m on metallic sheet and 7.1 m on plastic with the highest read distance of 9.3 m on a glass sheet. Also, the measurement setup along with developed WTMiddleware was deployed in an actual workplace to demonstrate practical utility of the designed tag affixed on workers’ safety helmets. It was observed that all the workers wearing tagged helmets were successfully identified, tracked, and monitored. Also, their real-time on-site details, working zone, and complete personal details were accessed through a developed web page application via WTMiddleware.